Collaborative design of a multi-functioning building envelope - Rockwood, David (ARCC Conference Repository, 2014)
This paper details the design evolution of a multi-functioning building envelope. The range of functions and performance achieved by the envelope were the result of close collaboration of faculty, students, and external consultants in architecture, electrical engineering, mechanical engineering, structural engineering, composite materials science, lighting design, and computer science. The envelope was designed with particular attention to tropical climate conditions. Negative factors, such as high heat, humidity, material degradation (e.g., rot, termites, rust), floods, and hurricanes were considered. At the same time, the tropics typically provide high insolation levels and potential for energy harvesting. A main focus of the research was to investigate the unique conditions present in tropical climates and to evolve responsive building envelope design in order to increase human comfort and lower energy use in this large world region. The envelope is comprised of: (a) semi-monocoque shell structure with tension bracing, (b) thermally-broken stressed FRP interior/exterior skins, (c) aerogel cavity granular insulationen capsulated in polycarbonate panels, (d) computer-controlled color-changeable LED lightstrips, (e) variable cavity ventilation system, and, (f) external photovoltaic computer-controlledlouvers. These elements were designed to have the following attributes and functions: (a)lightweight structure for minimal material use, (b) watertight enclosure for flotation, (c) minimalthermal envelope gains/losses, (d) variable daylighting, (e) variable artificial lighting color,intensity, position, and pattern, and, (f) variable incident PV angle for optimal energy harvesting. The steps in discovering, understanding, and capitalizing on the various and synergistic relationships among materials, assemblies, and systems to achieve high-level performance design objectives are detailed. The paper uses the specific case of a building envelope design to argue for the more general need to assemble collaborative relationships in order to provide multi-functionality and systems synergy and to thereby achieve higher levels of performance and materials/system efficiency.